Analysis of young students' perception of loneliness: a cross-sectional study - Hernández-Díaz, Rogelio; Navarro-Vásquez, Lucas; Aguilar-Latorre, Alejandra; Méndez-López, Fátima; Gascón-Santos, Santiago; Magallón-Botaya, Rosa (Frontiers in Psychology, 2025)
IntroductionLoneliness, a multidimensional emotional experience resulting from unmet social needs, affects individuals across demographics and is particularly prevalent among youth. It can be social or emotional and is linked to developmental transitions, reduced social networks, mental health conditions, and excessive social media use. Unlike desired solitude, loneliness is involuntary and associated with significant physical and mental health risks, including depression, suicide, and chronic illnesses. Despite its public health impact, youth loneliness remains underrecognized, necessitating tailored interventions. This study examines its prevalence and relationship with sociodemographic factors, social support, social media use, self-esteem, and health among students in Aragon.MethodsThis cross-sectional study investigated loneliness among adolescents and young adults (14–30 years) studying in Zaragoza, Spain, using online surveys conducted in March–April 2024. A sample of 536 participants was selected based on inclusion criteria, including informed consent. Loneliness was assessed using the UCLA Loneliness Scale and the De Jong Gierveld Loneliness Scale, alongside sociodemographic, social, and psychological variables such as self-esteem, health, mental health, and social media use. Descriptive, correlational, and regression analyses were performed to identify predictors of loneliness.ResultsThe study sample comprised 73.7% women, with an average age of 20 years. Among participants, 45.9% were high school students and 54.1% university students. Higher loneliness levels are associated with spending more time on social media, fewer and lower-quality relationships, lower self-esteem, poorer self-perceived health, and having mental health problems. While no significant gender or age differences were found, the UCLA Loneliness Scale identified 31.2% of participants as lonely, and the De Jong Gierveld Loneliness Scale classified 49.1% with moderate loneliness and 27.1% with severe loneliness.DiscussionThis study highlights the high prevalence of loneliness among young individuals, affecting approximately two-thirds of the population aged 14–30. The findings underscore the importance of addressing loneliness as a public health concern, with particular attention to vulnerable groups. Further research is needed to develop effective prevention, detection, and intervention strategies tailored to youth, which could be implemented through Primary Care and educational institutions.